2021
DOI: 10.1080/10615806.2021.1946518
|View full text |Cite
|
Sign up to set email alerts
|

The moderating effects of reported pre-pandemic social anxiety, symptom impairment, and current stressors on mental health and affiliative adjustment during the first wave of the COVID-19 pandemic

Abstract: I would like to thank my supervisor, Dr. David Moscovitch, for his endless support and guidance in my research work so far and throughout the Master's degree. I have especially admired his immense commitment to communication and collaboration-particularly in the face of a global pandemic-and value the openness that he has shown towards my thoughts and ideas. I would further like to thank my thesis readers, Dr. Christine Purdon and Dr. Jonathan Oakman, for their time and effort in providing valuable feedback on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 85 publications
2
17
0
2
Order By: Relevance
“…Additionally, social anxiety severity was indeed associated with poorer functioning per reports on the Social Distancing and Contamination domains of the FIVE. Findings from this study align with previous reports of lower QoL ratings in individuals with higher social anxiety ( Eng et al, 2001 ), as well as work suggesting that social anxiety is related to worse functioning during COVID-19 (e.g., Ho & Moscovitch, 2021 ; Quittkat et al, 2020 ); however, it should be noted that the Behaviors Related to Illness and Impact of Illness domains of the FIVE were not significantly correlated with social anxiety. These results suggest that targeting social anxiety may help improve specific facets of QoL and functioning during COVID-19.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Additionally, social anxiety severity was indeed associated with poorer functioning per reports on the Social Distancing and Contamination domains of the FIVE. Findings from this study align with previous reports of lower QoL ratings in individuals with higher social anxiety ( Eng et al, 2001 ), as well as work suggesting that social anxiety is related to worse functioning during COVID-19 (e.g., Ho & Moscovitch, 2021 ; Quittkat et al, 2020 ); however, it should be noted that the Behaviors Related to Illness and Impact of Illness domains of the FIVE were not significantly correlated with social anxiety. These results suggest that targeting social anxiety may help improve specific facets of QoL and functioning during COVID-19.…”
Section: Discussionsupporting
confidence: 88%
“… Quittkat and colleagues (2020) demonstrated that adults with SAD reported higher stress during the pandemic as compared to before; however, they did not find an increase in disorder-specific SAD symptom severity. In the second study, Ho and Moscovitch (2021) reported that pre-existing social anxiety symptoms predicted coronavirus-specific anxiety, loneliness, fears of negative evaluation, use of preventative approaches, and affiliative outcomes. In this investigation, it was further demonstrated that the presence of social anxiety symptomatology prior to the emergence of COVID-19 predicted poorer mental health functioning, higher levels of loneliness, and greater fear of negative evaluation during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of this affiliative tendency after acute stress is widespread, including after the 9/11 terrorist attack (Morgan et al, 2011), the Virginia Tech campus shootings (Mancini et al, 2016), hurricane exposure (Mancini et al, 2021;Williamson et al, 2021), earthquakes (Prati et al, 2013), and the Fukushima nuclear disaster (Uchida et al, 2014). With specific relevance to COVID-19 pandemic, the severe acute respiratory syndrome epidemic in Hong Kong in 2003 resulted in increased feelings of embeddedness in the community and caring for friends and family members (Lau et al, 2008;Lau et al, 2006), and similar findings have emerged for the COVID-19 pandemic (Ho & Moscovitch, 2022;Yang et al, 2021). Together these findings suggest that social-affiliative behavior is a normative response to perceived stress and may distinguish more adaptive responses to stress.…”
mentioning
confidence: 81%
“…For COVID-19 WORRY AND WELL-BEING example, worries about the health and well-being of friends and family would likely prompt affiliative behavior to see how they are doing. Indeed, such social overtures have been extensively documented during the COVID-19 and previous pandemics (Ho & Moscovitch, 2022;Lau et al, 2006;Yang et al, 2021). Because social relationships and social behavior directly benefit well-being (Baumeister & Leary, 1995;Diener et al, 2018;Lakey & Orehek, 2011;Lucas & Dyrenforth, 2006), one plausible consequence of social-affiliative behavior is improved well-being.…”
Section: Social Benefits and Psychological Costs Of Normative Worrymentioning
confidence: 99%
“…Positive outcomes primarily entailed staying connected with friends, peers and colleagues through platforms such as Zoom, Webex or WhatsApp. Additionally, for some, not having to deal with the potential social anxiety of in-person socialization was beneficial when being able to use more streamlined online interactions (Ho & Moscovitch, 2021).…”
Section: Emerging Evidencementioning
confidence: 99%